2004
DOI: 10.1021/bc049919o
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium(II)−Phenanthroline−Biotin Complexes:  Synthesis and Luminescence Enhancement upon Binding to Avidin

Abstract: We report the synthesis, characterization, and avidin-binding properties of two novel ruthenium complexes, [Ru(bpy)(2)(phen-biotin)][PF(6)](2) 1 and [Ru(phen)(2)(phen-biotin)][PF(6)](2) 2 (bpy = 2,2'-bipyridine; phen = 1,10-phenanthroline, phen-biotin = 5-(10-amidobiotinyl)-1,10-phenanthroline)). We demonstrate that both biotinylated compounds bind to avidin through their biotin moieties with high affinity and in a 4:1 ratio. The binding of compounds 1 and 2 to avidin results in an enhancement in luminescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 38 publications
1
32
0
Order By: Relevance
“…[29] We have previously attached phen-biotin (2) to ruthenium(II) bis-bipyridine (RuA C H T U N G T R E N N U N G (bpy)), have shown that the resulting complex displays high binding affinity to streptavidin, and that its luminescence is enhanced upon binding. [35] For the intercalating portion of the molecule, we selected dipyridophenazine (DPPZ) as an extended aromatic moiety. Ruthenium-DPPZ (Ru-A C H T U N G T R E N N U N G (dppz)) complexes have been pioneered by the laboratory of Barton et al as "molecular light switches", the luminescence of which is undetectable in water, but is turned "on" in the presence of double-stranded DNA (K d~1 0 À6 m).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[29] We have previously attached phen-biotin (2) to ruthenium(II) bis-bipyridine (RuA C H T U N G T R E N N U N G (bpy)), have shown that the resulting complex displays high binding affinity to streptavidin, and that its luminescence is enhanced upon binding. [35] For the intercalating portion of the molecule, we selected dipyridophenazine (DPPZ) as an extended aromatic moiety. Ruthenium-DPPZ (Ru-A C H T U N G T R E N N U N G (dppz)) complexes have been pioneered by the laboratory of Barton et al as "molecular light switches", the luminescence of which is undetectable in water, but is turned "on" in the presence of double-stranded DNA (K d~1 0 À6 m).…”
Section: Resultsmentioning
confidence: 99%
“…Some of these complexes were shown to bind DNA and avidin in separate experiments, but cross-linking of the two molecules was not demonstrated. [36,37] 6 ] 2 ) was synthesized by coupling RuA C H T U N G T R E N N U N G (dppz) 2 Cl 2 [38] and phen-biotin (2) [35] in ethylene glycol/water, followed by precipitation with NH 4 [39] was first coupled with the acyl chloride derivative of biotin. [40] The DPPZ-biotin ligand was then treated with RuA C H T U N G T R E N N U N G (bpy) 2 Cl 2 [41] and complex 3 was obtained as a PF 6 À salt (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent ruthenium(II) complexes are of interest of due to their applications in photochemical molecular devices (PMD) such as OLED devices, dye-sensitized solar cells (DSSC), photosensitizers in artificial photosynthesis, sensors, DNA dynamic probes, lipid probes and fluorescence polarization immunoassays (FPI) [1][2][3][4][5][6][7][8][9][10][11]. Recent descriptions of the photochemistry of coordination compounds of ruthenium(II) indicate that they can fulfill many of the functions necessary for these devices [1].…”
Section: Introductionmentioning
confidence: 99%
“…Recent descriptions of the photochemistry of coordination compounds of ruthenium(II) indicate that they can fulfill many of the functions necessary for these devices [1]. One of the most studied classes of ruthenium(II) complexes are polypyridine complexes [11][12][13][14][15]. In these species, strong emission in ambient temperature solutions is attributed to 3 MLCT states, but the photophysics and photochemistry of cationic polypyridine complexes depend also on the accessibility of short lived (s = 5 -20 ns or less) 3 MC states [1].…”
Section: Introductionmentioning
confidence: 99%